Big data analytics for improved accuracy, efficiency, and decision making in digital marketing - Singh, Amandeep, 1982- (Business Science Reference, 2021)
"This book will help the digital marketers to understand the Big Data in a better way and to get a meaning full information, which, will help the marketers to better market their products to the consumers"--